Pengaruh Media Digital terhadap Variasi Bahasa di Kalangan Mahasiswa - Hidayatul Umiro; Syahrul Ramadhan; Norliza Jamaluddin (Lembag, 2025)
This study aims to explore the influence of digital media on language variation among college students. Using qualitative methods and a literature review design, this study analyzes how digital media, such as social media, online communication platforms, and instant messaging applications, influence language use among college students. The results show that digital media triggers the emergence of language variation that includes digital slang, changes in grammar and spelling, and the transfer of foreign culture and vocabulary. Although digital media provides a space for students to express themselves creatively, there are concerns about the negative impact on formal language proficiency. Therefore, this study emphasizes the importance of collaborative efforts from educational institutions and students to maintain a balance between linguistic creativity and the preservation of formal language.